Avoidance of gender-ambiguous pronouns as a consequence of ambiguity-avoidance strategy. Issue 3 (16th March 2021) - Hwang, Heeju
ABSTRACT: It is well known that English speakers produce fewer pronouns when discourse contexts include more than one entity that matches the gender of the pronoun, i.e., gender effect. It is controversial, however, what causes the gender effect. Some suggest that it results from speakers' avoidance of linguistic ambiguity, while others suggest that it results from the influence of non-linguistic conceptual similarity between discourse entities. To adjudicate between the two accounts, the present study investigates how Mandarin speakers choose referring expressions in written and spoken Mandarin. As written and spoken Mandarin differ in their referential ambiguity (the third-person singular pronoun is gender-ambiguous in spoken Mandarin but not in written Mandarin), it provides a good testing ground for evaluating the two accounts with the manipulation of gender similarity. We found that Mandarin speakers' pronoun use was affected by pronoun ambiguity but not by conceptual similarity of discourse entities. In particular, in written Mandarin, where pronouns are gender-specific, Mandarin speakers produced fewer pronouns when there was more than one character that matched the gender of the pronoun. In spoken Mandarin where pronouns are gender-ambiguous, however, Mandarin speakers' pronoun use was not influenced by gender of discourse characters. Our findings suggest that the gender effect is driven by an ambiguity-avoidance strategy rather than conceptual similarity between discourse characters.